2013
DOI: 10.1111/joes.12010
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Link Between Financial Incentives and Weight Loss: An Evidence‐based Survey of the Literature

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
(74 reference statements)
3
23
0
Order By: Relevance
“…The experiment demonstrated that a positive, output-based financial incentive is an effective instrument to achieve a significant weight loss among the obese, consistent with what has been found in a number of previous studies [Paloyo et al 2014]. However, a general heterogeneity in the treatment effect of financial incentives is neither observed for socioeconomic characteristics nor for exhibited health-related behaviors in the study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The experiment demonstrated that a positive, output-based financial incentive is an effective instrument to achieve a significant weight loss among the obese, consistent with what has been found in a number of previous studies [Paloyo et al 2014]. However, a general heterogeneity in the treatment effect of financial incentives is neither observed for socioeconomic characteristics nor for exhibited health-related behaviors in the study.…”
Section: Discussionsupporting
confidence: 89%
“…Input-based incentives are typically tied to better diet and an active physical lifestyle, which are generally harder or at least more costly to observe than a simple measure of one's weight on a particular date. (A taxonomy of incentive designs is provided in Paloyo et al [2014]. )…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since participants in Kramer et al (1986) received not only the financial-incentive treatment, but also interacted with each other during discussion meetings, the effect of the deposit cannot be singled out. Further limitations of the study are discussed in Paloyo et al (2013).…”
Section: Introductionmentioning
confidence: 99%